PERENCANAAN JALAN BETON TANPA TULANGAN PADA KAWASAN INDUSTRI KRAKATAU STEEL KOTA CILEGON - Telly Rosdiyani; M Ichwanul Yusuf; Ibnu Haritz (LPPM, 2019)
In increasing the mobilization of vehicle movements, roads are an important means in order to smoothen land transportation, so that it can provide comfort and safety. The Industrial Area of ​​PT Krakatau Steel, Serang City, which is often passed by heavy vehicles, needs to be well planned according to the standards and criteria applicable in Indonesia. From a visual observation of the road in the area of ​​the Industrial Park, there is a lot of damage by finding deflections which are dangerous and can hamper the rate of transportation, so that road repairs and improvements are needed. The purpose of the study was to plan a continuous concrete pavement without reinforcement by knowing the thickness of the plate, the diameter of the dowel test and to know the drainage dimensions. The method carried out by field observation to obtain primary and secondary data as the basis for the concrete road planning material. The calculation method is used Binamarga T-14-2002 Guidelines with Concrete without Reinforcement (BBTT). The results of the calculation of the number of planning vehicles in traffic data with a planned 20-year lifespan for the 6% traffic growth rate obtained the thickness of concrete road pavement of 20 cm, dowel 33mm diameter for 300 mm distance and 450 mm length able to withstand crossing loads, with drainage dimensions 0.75 m channel width road, 1 m channel height and 0.70 m height guard have met the requirements for safe number stability.